Stabilitas Fisikokimia dan Efektivitas Kandidat Obat Kumur Ekstrak Biji Kopi Robusta (Coffea canephora) dengan Penambahan Minyak Atsiri Peppermint (Mentha piperita L.) Sebagai Antibakteri Terhadap Streptococcus mutans - Esa Kesuma Prastika (Fakultas Kedokteran Gigi, 2024)
Streptococcus mutans is a plevalent bacterium in dental plaque; hence the utilisation of herbal mouthwash is essential for plaque management. Robusta coffee bean extract has active compounds are chlorogenic acid, trigonelline, flavonoids, and tannins as an antibacterials, so potential to be formulated into a mouthwash candidate. Robusta coffee bean extract possesses a bitter, sour flavour and an unpleasant aroma, therefore it is advisable to use peppermint, which offers a refreshing taste and fragrance. According to BPOM RI, a quality mouthwash should have a pH of 5-7, maintain the stability 1-2 years post-producing, and possess a viscosity comparable to that of water, specifically 0.87-1 cP. The type of this research is laboratory experimental and analytical observational aims to test the physicochemical stability of mouthwash candidate and antibacterial test against S. mutans. The mouthwash candidate was prepared in 4 total concentrations: 3,125 g/mL, 6,25 g/mL, 12,5 g/mL, 25 g/mL. The physicochemical stability test included a real-time testing approach with storage at ambient temperature, assessed on days 0, 7, 14, and 21. The antimicrobial assay employed the well-diffusion technique. The data analysis employed a One-Way ANOVA test, succeeded by the LSD and Games-Howell tests. The physicochemical stability test results indicated that all mouthwash candidates exhibited favourable and stable pH, viscosity, and organoleptic qualities. The antibacterial test results indicated that the mouthwash candidate at a total concentration of 3.125 g/mL produced an inhibition zone of 23.56 mm, while the 6.25 g/mL concentration yielded 21.36 mm, the 12.5 g/mL concentration resulted in 19.08 mm, and the 25 g/mL concentration generated 19.56 mm. The positive control exhibited an inhibition zone of 10.44 mm, whereas the negative control displayed no inhibition zone. The mouthwash candidate exhibiting consistent physicochemical properties and optimal antibacterial efficacy has a total concentration of 3.125 g/mL.
Reuploud Repository hasyim Juni 2026 :: Finalisasi Repositori File 10 Juni 2026_Kurnadi
Keywords: Robusta coffee bean; peppermint; physicochemical stability test; S. mutans